Bat evolution, ecology, and conservation - Pedersen, Scott C.; Adams, Rick A. (Springer New York, 2013)
Recent advances in the study of bats have changed the way we understand this illusive group of mammals. This volume consist of 25 chapters and 57 authors from around the globe all writing on the most recent finding on the evolution, ecology and conservation of bats. The chapters are not intended to be exhaustive literature reviews, but instead extended manuscripts that bring new and fresh perspectives. Many chapters consist of previously unpublished data and are repetitive of new insights and understanding in bat evolution, ecology and conservation. New perspectives are provided on many aspects of bat biology, evolution, morphology, development, natural history, cognition and behavior, emotions, formation flight, migration, dispersal to islands, emerging viruses, white-nose syndrome, speciation, bats and the human dimension, educational and conservation challenges, global monitoring, economic value, and the state of global bat populations.  This book will be of interest to students, professional biologists, wildlife managers, conservationists, educators, environmental consultant, and anyone else interested in the broad and rich array of topics brought to date in this volume.